Analysis of skeletal muscle microcirculation in a porcine polytrauma model with haemorrhagic shock. Issue 5 (14th March 2018) - Qiao, Zhi; Horst, Klemens; Teuben, Michel; Greven, Johannes; Yin, Luxu; Kalbas, Yannik; Tolba, René H.; Pape, Hans‐Christoph; Hildebrand, Frank; Pfeifer, Roman
ABSTRACT: Polytraumatised patients with haemorrhagic shock are prone to develop systemic complications, such as SIRS (systemic inflammatory response syndrome), ARDS (acute respiratory distress syndrome) and MOF (multiple organ failure). The pathomechanism of severe complications following trauma is multifactorial, and it is believed that microcirculatory dysfunction plays an important role. The aim of this study was to determine the changes in the microcirculation in musculature over time during shock and subsequent resuscitation in a porcine model of haemorrhagic shock and polytrauma. Twelve pigs (German Landrace) underwent femur fracture, liver laceration, blunt chest trauma, and haemorrhagic shock under standard anaesthesia and intensive care monitoring. Microcirculation data were measured from the vastus lateralis muscle using a combined white light spectrometry and laser spectroscopy system every 15 min during the shock and resuscitation period, and at 24, 48, and 72 h. Oxygen delivery and oxygen consumption were calculated and compared to baseline. The relative haemoglobin, local oxygen consumption, and saturation values in the microcirculation were observed significantly lower during shock, however, no changes in the microcirculatory blood flow and microcirculatory oxygen delivery were observed. After resuscitation, the microcirculatory blood flow and relative haemoglobin increased and remained elevated during the whole observation period (72 h). In this study, we observed changes in microcirculation during the trauma and shock phases. Furthermore, we also measured persistent dysfunction of the microcirculation over the observation period of 3 days after resuscitation and haemorrhagic shock. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1377–1382, 2018.